The Effect of Limited Face-to-Face Learning in New Normal Era towards Learning Motivation of Elementary School Students - Rossy Arlinda; Wuri Wuryandani; Ali Mustadi (STAI Hubbulwathan Duri, 2022)
The purpose of this research is to measure the implementation effect of limited face-to-face learning in the new normal era towards elementary school student learning motivation. This research used an ex- post facto approach. The research population is fifth-grade students in Gugus Alalak, Banjarmasin, Indonesia total number of 296 students. The research sample was taken using a simple random sampling technique with a total of 183 fifth-grade students in the Alalak cluster, Banjarmasin, Indonesia. The data collection used are questionnaires given to 183 fifth grade students and interviews with 6 teachers in fifth grade. The data analysis technique used is descriptive statistical analysis and inferential analysis. Research findings show that the online learning process and change to limited face-to-face learning turn out to have an effect on students' learning motivation at school, in limited face-to-face learning students also become more motivated in learning.